The Concept of The Other as Constructed in Bharati Mukherjee's 'Desirable Daughters' - Karim, Mutiah; Margawati, Prayudias (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2020)
Dichotomy of the West and the East has become an issue after colonial era ended. The colonized countries such as India are seen as inferior to the Western countriesÃ¢â‚¬â€European countries and America. Moreover, according to Orientalism by Edward Said, the Westerners regard the East as The Other. This study aimed to explain (1) the concept of The Other as constructed in MukherjeeÃ¢â‚¬â„¢s Desirable Daughters and (2) how it affects the personality of the main characters. Observation sheets were used as research instrument and the data were obtained from library research. This qualitative descriptive study employed Orientalism theory by Edward Said in analyzing the data. It is found that the concept of The Other in MukherjeeÃ¢â‚¬â„¢s Desirable Daughters are constructed on three (3) keys which are (1) Westerners perspective on Indian people as well as Indian perspective on the Westerners, (2) the otherness of India, (3) and the imagery of India. Meanwhile, the construction of The Other has affected the main charactersÃ¢â‚¬â„¢ personality. From the construction of The Other, Indian are seen as inferior, powerless, poor, restricted, and traditional. It shows that Western hegemony can even change peopleÃ¢â‚¬â„¢s personality and how they think about their identity. Keywords: concept, desirable daughters, orientalism, the other